Teaching Business Models: Approaches and Success Criteria - Christina Bidmon; Anna B. Holm (Journal of Business Models, 2021)
Teaching business models (BM) and business model innovation (BMI) in universities and business schools has become a common practice. Academia has acknowledged that despite the very normative nature of the concept, business model thinking unites and synergistically binds the very fundamental decisions about a business, i.e., how to create, deliver and capture value.